The cellular antiviral restriction factor tetherin does not inhibit poxviral replication - Sliva, Katja; Laqmani-Goffinet, Christine; Keppler, Oliver Till (Journal of virology, 2012)
Interferon-stimulated genes fulfill innate antiviral effector functions. Among them, tetherin (THN) blocks the release of many enveloped viruses from infected cells. Vaccinia virus (VACV) encodes immune modulators interfering with antiviral host responses. Therefore, it was tempting to study a potential VACV-THN interaction. Remarkably, THN expression did not inhibit VACV release and replication. VACV infection did not diminish THN surface levels or impair its function on retroviral release. This suggests that THN is unable to restrict VACV replication.
Published ahead of print 16 November 2011
Gesehen am 09.07.2019